Environment-friendly anti-skid plastic track material and preparation method thereof
By preparing a compound of modified carbon fiber and zinc oxide nanosheets with anti-skid and wear-resistant fillers, the problem of decreased anti-skid and wear-resistant performance of plastic track materials was solved, and the long-term anti-skid and wear-resistant performance and impact resistance of the material were improved.
Patent Information
- Application Number
- CN202511260594.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-04
- Publication Date
- 2025-10-17
AI Technical Summary
The anti-slip and wear-resistant performance of plastic track materials decreases during long-term use, and the anti-slip and wear-resistant fillers have poor compatibility with plastic track materials, affecting the anti-slip and wear-resistant performance.
Graphene oxide is treated with silane and then mixed with silane, modified carbon fiber and lauryl methacrylate to prepare anti-slip and wear-resistant fillers. The modified carbon fiber and zinc oxide nanosheets are compounded to form a three-dimensional structure, thereby enhancing the anti-slip and wear-resistant properties of the plastic track material.
It improves the anti-skid and wear-resistant properties of the plastic track material, enhances the impact resistance and load-bearing capacity, extends the service life, and avoids the agglomeration and precipitation of the anti-skid and wear-resistant fillers and structural damage.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of plastic track materials, in particular to an environment-friendly anti-skid plastic track material and a preparation method thereof. BACKGROUND
[0002] The plastic track is usually formed by mixing granular plastic track material with a binder and then paving on a cement or asphalt ground. The formed plastic track has good flatness, high compressive strength and large friction, and has good anti-skid performance. The formed plastic track has small toxicity, small harm to human health, small influence on the environment and other advantages, which meets the environmental protection needs. In addition, the plastic track is not affected by temperature and humidity, drains quickly, and can be quickly put into use after rain, which is also called all-weather sports ground, and ensures the sports experience of athletes.
[0003] The plastic track material prepared by adding a toughening agent, a filler and a foaming agent to hyperbranched polyethylene as a base material has high anti-skid and wear-resistant performance and excellent mechanical strength. However, the prepared plastic track material has large wear on the plastic track during long-term use, which leads to a decrease in anti-skid performance. By adding an anti-skid and wear-resistant filler, the long-term anti-skid and wear-resistant performance of the plastic track material can be significantly improved. However, the anti-skid and wear-resistant filler has poor compatibility with the plastic track material, which leads to easy agglomeration and precipitation of the anti-skid and wear-resistant filler, thereby affecting the anti-skid and wear-resistant performance of the plastic track. SUMMARY
[0004] The present application provides an environment-friendly anti-skid plastic track material and a preparation method thereof, which solves the problems of poor anti-skid and wear-resistant performance of the plastic track material and poor compatibility of the anti-skid and wear-resistant filler with the plastic track material.
[0005] The technical scheme of the present application is as follows: An environment-friendly anti-skid plastic track material comprises the following raw materials by mass: 50-55 parts of hyperbranched polyethylene, 10-15 parts of anti-skid and wear-resistant filler, 5-8 parts of plastic toughening agent, 45-50 parts of inorganic filler, 1-2 parts of plastic foaming agent and 1-2 parts of dispersant. The anti-skid and wear-resistant filler is obtained by mixing and reacting graphene oxide treated with silane, silane, modified carbon fiber and lauryl methacrylate. The modified carbon fiber is obtained by synthesizing zinc oxide nanosheets on the surface of calcium carbonate particles and then depositing tannic acid on the surface of the carbon fiber. A preparation method of an environment-friendly anti-skid plastic track material comprises the following preparation steps: S1. Hyperbranched polyethylene, anti-skid and wear-resistant filler, plastic toughening agent, inorganic filler, plastic foaming agent and dispersant are uniformly mixed to obtain a mixture. S2. The mixture is extruded and granulated to obtain an anti-skid plastic track material.
[0006] Further, in step S1, the mixing temperature is 60-80℃, the mixing time is 3-10min, and the mixing speed is 600-800r / min.
[0007] Further, in step S2, the extrusion is performed by using a double-screw extruder, the temperature of the extruder barrel and die head is 150-200℃, and the screw rotation speed is 200-500r / min.
[0008] Further, the anti-skid plastic runway material has a particle size of 3-5mm.
[0009] Further, the hyperbranched polyethylene has a degree of branching of 20-25 methyl branches per 1000 carbons and a weight average molecular weight of 100-200 thousand.
[0010] Further, the plastic toughening agent is selected from styrene-ethylene-butylene-styrene block copolymer or styrene-butadiene-styrene block copolymer.
[0011] Further, the inorganic filler is selected from any one of talc, kaolin, and white carbon black.
[0012] Further, the plastic foaming agent is AC foaming agent or ADC foaming agent.
[0013] Further, the dispersant is stearic acid or glycerol stearate.
[0014] Further, the anti-skid wear-resistant filler is prepared by the following steps: A1. Zinc nitrate hexahydrate is added to deionized water, stirred uniformly, heated to 70-80℃, potassium hydroxide and calcium carbonate particles are added, stirred uniformly, dodecyl trimethyl ammonium bromide is added, continued stirring, after standing, filtration, washing, drying, to obtain calcium carbonate particles loaded with nanosheets; A2. Tannic acid is added to ethanol, stirred until completely dissolved, carbon fibers are added, after stirring, the calcium carbonate particles loaded with nanosheets are added, continued stirring, filtration, washing, drying, to obtain modified carbon fibers; A3. Graphene oxide and n-butylamine are mixed, stirred uniformly, toluene is added, ultrasonic treatment, silane is added, continued ultrasonic treatment, stirring reaction, centrifugal collection of precipitate, precipitate washing, drying, to obtain modified graphene oxide; A4. Modified carbon fibers, silane are added to ethanol and deionized water, after stirring reaction, cooling to room temperature, filtration, washing, drying, to obtain double bond modified carbon fibers; A5. Double bond modified carbon fibers, modified graphene oxide, and lauryl methacrylate are added to ethanol, stirred uniformly, azobisisobutyronitrile is added, nitrogen is introduced, after stirring reaction, filtration, washing, drying, to obtain the anti-skid wear-resistant filler.
[0015] Further, in the above-mentioned A1 reaction process, the calcium carbonate particles have hydrophilicity, and a large number of hydroxyl groups on the surface of the calcium carbonate particles can combine with zinc ions in zinc nitrate hexahydrate. The zinc ions react with potassium hydroxide to form hydroxide which is deposited on the surface of the calcium carbonate particles. The hydroxide is hydrothermally decomposed at 70°C to form zinc oxide crystals. Dodecyltrimethylammonium bromide as a surfactant is coated on the surface of the zinc oxide crystals to form steric hindrance, control the growth direction of the zinc oxide crystals, and realize the synthesis of petal-shaped zinc oxide nanosheets on the surface of the calcium carbonate particles, thereby obtaining calcium carbonate particles loaded with nanosheets.
[0016] Further, in the above-mentioned A2 reaction process, tannic acid contains a large number of phenolic hydroxyl groups and has good adhesion performance, so that the tannic acid adheres to the surface of the carbon fiber, and then the calcium carbonate particles loaded with nanosheets can be adhered to the surface of the carbon fiber, thereby obtaining the modified carbon fiber.
[0017] Further, in the above-mentioned A3 reaction process, the ultrasonic treatment does not destroy the layered structure of the graphene oxide, so that the silane can be intercalated between the layers of the graphene oxide, and the silicon hydroxyl groups generated by the hydrolysis of the silane can be combined with the oxygen-containing functional groups on the surface and between the layers of the graphene oxide through chemical bonds, thereby maintaining the layered structure of the graphene oxide, realizing the intercalation and surface silanization of the graphene oxide, and obtaining the modified graphene oxide.
[0018] Further, in the above-mentioned A4 reaction process, the silicon hydroxyl groups generated by the hydrolysis of the silane can be combined with the hydroxyl groups on the surface of the modified carbon fiber, so that the silane is grafted on the surface of the modified carbon fiber, thereby endowing the modified carbon fiber with reactive double bonds.
[0019] Further, in the above-mentioned A5 reaction process, azobisisobutyronitrile as an initiator makes the double bonds of the double-bond modified carbon fiber, the double bonds of the surface silane of the modified graphene oxide, and the double bonds of the lauryl methacrylate copolymerize to form a terpolymer, thereby realizing the deposition of the modified graphene oxide on the surface of the modified carbon fiber through the terpolymer, and obtaining the anti-skid and wear-resistant filler.
[0020] Further, in step A1, the mass ratio of zinc nitrate hexahydrate, deionized water, potassium hydroxide, calcium carbonate particles, and dodecyltrimethylammonium bromide is (3-3.4):(90-110):(1.2-1.6):(4-5):(0.3-0.7).
[0021] Further, in step A2, the mass ratio of tannic acid, ethanol, carbon fiber, and calcium carbonate particles loaded with nanosheets is (0.6-1):(45-50):(4-4.5):(2.5-2.9).
[0022] Further, in step A3, the mass ratio of graphene oxide, n-butylamine, toluene and silane is (1.4-1.6):(13-17):(80-90):(3-4).
[0023] Further, in step A4, the mass ratio of modified carbon fiber, silane, ethanol and deionized water is (4-5):(0.6-0.8):(25-30):(8-12).
[0024] Further, in step A5, the mass ratio of double bond modified carbon fiber, modified graphene oxide, lauryl methacrylate, ethanol and azobisisobutyronitrile is (4-5):(3-4):(4-4.5):(130-150):(0.1-0.3).
[0025] Further, the particle size of calcium carbonate particles is 40-60nm.
[0026] Further, the diameter of carbon fiber is 1-2µm, and the length is 8-15µm.
[0027] Further, the flake diameter of graphene oxide is 4-8µm.
[0028] Further, the silane used in step A3 and step A4 is gamma-methacryloxypropyltrimethoxysilane.
[0029] The present application has the following beneficial effects: (1) In the technical scheme of the present application, petal-shaped zinc oxide nanosheets are synthesized on the surface of calcium carbonate particles. On the one hand, the surface of calcium carbonate particles has dense petal-shaped zinc oxide nanosheets, which can exert a "mechanical interlocking" effect, generate greater resistance, improve the friction coefficient, and thus enhance the anti-skid performance of the plastic track material. Moreover, the calcium carbonate particles compounded with zinc oxide nanosheets can form a rough structure on the surface of the plastic track, improving the friction coefficient. On the other hand, the petal-shaped zinc oxide nanosheets have a three-dimensional structure formed by the interlaced connection of nanosheets, which can effectively disperse pressure, reduce local wear, and improve the wear resistance of the plastic track material.
[0030] (2) In the technical scheme of the present application, the calcium carbonate particles loaded with nanosheets are deposited on the surface of carbon fibers through tannic acid. On the one hand, carbon fibers have excellent length-diameter ratio and are randomly distributed in the plastic track material to form a network structure capable of absorbing and weakening external pressure. The thickness of the petal-shaped zinc oxide nanosheets on the surface of the calcium carbonate particles loaded with nanosheets is relatively thin, and the nanosheets are prone to breakage and shedding during long-term use, which affects the anti-skid and wear-resistant performance of the plastic track material. On the other hand, carbon fibers serve as carriers of the calcium carbonate particles loaded with nanosheets, improving the dispersibility of the calcium carbonate particles loaded with nanosheets. Moreover, carbon fibers have high tensile strength and elastic modulus, and when added to the plastic track material, they can significantly enhance the impact resistance and load-bearing capacity of the plastic track, making it less likely to crack or break due to external forces.
[0031] (3) In the technical scheme of the present application, graphene oxide is intercalated and surface silanized with γ-methacryloxypropyltrimethoxysilane, which tightly binds the graphene oxide layers through γ-methacryloxypropyltrimethoxysilane, maintaining the layered structure of graphene oxide and improving the wear resistance of the plastic track material. Moreover, the grafting of γ-methacryloxypropyltrimethoxysilane on the surface of graphene oxide facilitates the covalent grafting of graphene oxide on the surface of modified carbon fibers, producing a micro-ball effect that further enhances the wear resistance of the plastic track material and improves its service life.
[0032] (4) In the technical scheme of the present application, modified graphene oxide is deposited on the surface of modified carbon fibers through a terpolymer. On the one hand, the terpolymer coats the surface of modified carbon fibers, and the interlayer terpolymer acts as a lubricating component, allowing the modified graphene oxide to move back and forth on the surface of modified carbon fibers, producing a micro-ball effect that increases the buffer distance between modified graphene oxide and modified carbon fibers, thereby reducing the heat generated by friction in the composite material and achieving excellent wear resistance. On the other hand, the surface of the anti-skid and wear-resistant filler contains γ-methacryloxypropyltrimethoxysilane molecular chains, which improve the compatibility of the anti-skid and wear-resistant filler with the polyethylene-based plastic track material, enhancing the anti-skid and wear-resistant performance and mechanical properties of the plastic track. In addition, there are numerous gaps between the petal-shaped zinc oxide nanosheets on the surface of modified carbon fibers, allowing the long carbon molecular chains of lauryl methacrylate in the terpolymer to penetrate into the gaps between the nanosheets, forming an entangled network that improves the shear resistance and prevents structural damage to the anti-skid and wear-resistant filler during friction, thereby affecting the anti-skid, wear-resistant performance, and mechanical properties of the plastic track material. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present application will be clearly and completely described below with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by a person of ordinary skill in the art without creative work fall within the protection scope of the present application.
[0034] The raw materials used in the embodiments of the present application are shown below, and all the reagents used are analytical grade.
[0035] The hyperbranched polyethylene has a branching degree of 23 methyl branches per 1000 carbons and a weight average molecular weight of 150,000, and is a product with a trade name of 8916, which is purchased from Ningbo Shijin Plastics Co., Ltd.
[0036] The plastic toughening agent is a styrene-ethylene-butylene-styrene block copolymer, the plastic foaming agent is an AC foaming agent, the dispersing agent is stearic acid, and the inorganic filler is selected from talc with a particle size of 15 µm.
[0037] The calcium carbonate particles have a particle size of 50 nm.
[0038] The carbon fibers have a diameter of 1.5 µm and a length of 10 µm.
[0039] The graphene oxide sheets have a diameter of 6 µm.
[0040] The silanes used in steps A3 and A4 are all γ-methacryloyloxypropyltrimethoxysilane.
[0041] Embodiment 1 An environmentally friendly anti-skid plastic track material includes the following raw materials in parts by mass: 50 parts of hyperbranched polyethylene, 10 parts of anti-skid wear-resistant filler, 5 parts of styrene-ethylene-butylene-styrene block copolymer, 45 parts of talc, 1 part of AC foaming agent, and 1 part of stearic acid. A preparation method of an environmentally friendly anti-skid plastic track material includes the following preparation steps: S1. The hyperbranched polyethylene, the anti-skid wear-resistant filler, the styrene-ethylene-butylene-styrene block copolymer, the talc, the AC foaming agent, and the stearic acid are uniformly mixed, the mixing temperature is 60°C, the mixing time is 3 min, and the mixing speed is 600 r / min to obtain a mixture; S2. The mixture is extruded and granulated to obtain the anti-skid plastic track material, and a double-screw extruder is used for the extrusion, the temperature of the barrel and the die head of the extruder is 150°C, and the screw rotation speed is 200 r / min.
[0042] The anti-skid wear-resistant filler is prepared by the following steps: A1. Zinc nitrate hexahydrate was added to deionized water, stirred until uniform, heated to 70°C, potassium hydroxide and calcium carbonate particles were added, stirred for 30 min, dodecyl trimethyl ammonium bromide was added, continued to stir for 2 h, stood for 2 h, filtered, washed with deionized water for 3 times, dried in an oven at 70°C for 10 min, to obtain calcium carbonate particles loaded with nanosheets; the mass ratio of zinc nitrate hexahydrate, deionized water, potassium hydroxide, calcium carbonate particles and dodecyl trimethyl ammonium bromide was 3:90:1.2:4:0.3; A2. Tannic acid was added to ethanol, stirred until completely dissolved, carbon fibers were added, stirred at 50°C for 30 min, calcium carbonate particles loaded with nanosheets were added, stirred at 25°C, 800 r / min for 40 min, filtered, washed with deionized water for 3 times, dried in an oven at 70°C for 10 min, to obtain modified carbon fibers; the mass ratio of tannic acid, ethanol, carbon fibers and calcium carbonate particles loaded with nanosheets was 0.6:45:4:2.5; A3. Graphene oxide and n-butylamine were mixed, stirred at 60°C for 1 h, toluene was added, ultrasonically treated at 20 KHz for 30 min, γ-methacryloxypropyl trimethoxysilane was added, continued to ultrasonically treat for 30 min, then stirred at 110°C for 4 h, the precipitate was collected by centrifugation, the precipitate was washed with ethanol for 3 times, washed with acetone for 3 times, dried in an oven at 60°C for 12 h, to obtain modified graphene oxide; the mass ratio of graphene oxide, n-butylamine, toluene and γ-methacryloxypropyl trimethoxysilane was 1.4:13:80:3; A4. Modified carbon fibers and γ-methacryloxypropyl trimethoxysilane were added to ethanol and deionized water, stirred at 60°C for 2 h, cooled to room temperature, filtered, washed with deionized water for 3 times, then dried in an oven at 70°C for 10 min, to obtain double bond modified carbon fibers; the mass ratio of modified carbon fibers, γ-methacryloxypropyl trimethoxysilane, ethanol and deionized water was 4:0.6:25:8; A5. Double bond modified carbon fibers, modified graphene oxide and lauryl methacrylate were added to ethanol, stirred until uniform, azobisisobutyronitrile was added, nitrogen was introduced, stirred at 300 r / min, 60°C for 4 h, filtered, washed with deionized water for 3 times, then dried in an oven at 70°C for 10 min, to obtain anti-skid and wear-resistant filler; the mass ratio of double bond modified carbon fibers, modified graphene oxide, lauryl methacrylate, ethanol and azobisisobutyronitrile was 4:3:4:130:0.1.
[0043] Example 2 An environment-friendly anti-skid plastic track material comprises the following raw materials in parts by mass: hyperbranched polyethylene 53 parts, anti-skid wear-resistant filler 13 parts, styrene-ethylene-butylene-styrene block copolymer 7 parts, talcum powder 48 parts, AC foaming agent 1.5 parts, and stearic acid 1.5 parts; A preparation method of an environment-friendly anti-skid plastic track material comprises the following preparation steps: S1. The hyperbranched polyethylene, the anti-skid wear-resistant filler, the styrene-ethylene-butylene-styrene block copolymer, the talcum powder, the AC foaming agent, and the stearic acid are uniformly mixed at a mixing temperature of 70℃, a mixing time of 5 min, and a mixing speed of 700 r / min to obtain a mixture; S2. The mixture is extruded and granulated to obtain the anti-skid plastic track material, and a double-screw extruder is used for the extrusion, with the temperature of the barrel and the die head being 180℃ and the screw rotation speed being 350 r / min.
[0044] The anti-skid wear-resistant filler is prepared by the following steps: A1. Zinc nitrate hexahydrate is added to deionized water and stirred uniformly, heated to 75℃, and then potassium hydroxide and calcium carbonate particles are added and stirred and mixed for 30 min. Then, dodecyl trimethyl ammonium bromide is added and stirred for another 2 h, and then left to stand for 2 h. After filtration, the mixture is washed with deionized water for 3 times, and then dried in a 70℃ oven for 10 min to obtain calcium carbonate particles loaded with nanosheets. The mass ratio of zinc nitrate hexahydrate, deionized water, potassium hydroxide, calcium carbonate particles, and dodecyl trimethyl ammonium bromide is 3.2:100:1.4:4.5:0.5; A2. Tannic acid is added to ethanol and stirred until completely dissolved. Then, carbon fibers are added and stirred at 50℃ for 30 min. Then, calcium carbonate particles loaded with nanosheets are added and stirred at 25℃ and 800 r / min for 40 min. After filtration, the mixture is washed with deionized water for 3 times, and then dried in a 70℃ oven for 10 min to obtain modified carbon fibers. The mass ratio of tannic acid, ethanol, carbon fibers, and calcium carbonate particles loaded with nanosheets is 0.8:48:4.3:2.7; A3. Graphene oxide and n-butylamine are mixed and stirred at 60℃ for 1 h. Then, toluene is added and ultrasonically treated at 20 KHz for 30 min. Then, γ-methacryloyloxypropyl trimethoxysilane is added and ultrasonically treated for another 30 min. Then, the mixture is stirred at 110℃ for 4 h. The precipitate is collected by centrifugation, washed with ethanol for 3 times, and washed with acetone for 3 times. Then, the mixture is dried in a 60℃ oven for 12 h to obtain modified graphene oxide. The mass ratio of graphene oxide, n-butylamine, toluene, and γ-methacryloyloxypropyl trimethoxysilane is 1.5:15:85:3.5; A4. The modified carbon fiber, γ-methacryloxypropyltrimethoxysilane is added to ethanol and deionized water, stirred and reacted at 60℃ for 2h, cooled to room temperature, filtered, washed with deionized water for 3 times, and dried in an oven at 70℃ for 10min to obtain the double bond modified carbon fiber; the mass ratio of the modified carbon fiber, γ-methacryloxypropyltrimethoxysilane, ethanol and deionized water is 4.5:0.7:28:10; A5. The double bond modified carbon fiber, modified graphene oxide and lauryl methacrylate are added to ethanol, stirred and mixed uniformly, azobisisobutyronitrile is added, nitrogen is introduced, stirred and reacted at 300r / min and 60℃ for 4h, filtered, washed with deionized water for 3 times, and dried in an oven at 70℃ for 10min to obtain the anti-skid and wear-resistant filler; the mass ratio of the double bond modified carbon fiber, modified graphene oxide, lauryl methacrylate, ethanol and azobisisobutyronitrile is 4.5:3.5:4.6:140:0.2.
[0045] Example 3 An environment-friendly anti-skid plastic track material, comprising the following raw materials in parts by mass: hyperbranched polyethylene 55 parts, anti-skid and wear-resistant filler 15 parts, styrene-ethylene-butylene-styrene block copolymer 8 parts, talc 50 parts, AC foaming agent 2 parts, stearic acid 2 parts; A preparation method of an environment-friendly anti-skid plastic track material, comprising the following preparation steps: S1. The hyperbranched polyethylene, anti-skid and wear-resistant filler, styrene-ethylene-butylene-styrene block copolymer, talc, AC foaming agent and stearic acid are uniformly mixed, the mixing temperature is 80℃, the mixing time is 10min, and the mixing speed is 800r / min to obtain a mixture; S2. The mixture is extruded and granulated to obtain the anti-skid plastic track material, and a double screw extruder is used for extrusion, the temperature of the extruder barrel and die head is 200℃, and the screw rotation speed is 500r / min.
[0046] The anti-skid and wear-resistant filler is specifically prepared by the following steps: A1. Zinc nitrate hexahydrate is added to deionized water, stirred and mixed uniformly, heated to 80℃, potassium hydroxide and calcium carbonate particles are added, stirred and mixed for 30min, dodecyltrimethylammonium bromide is added, and stirred for another 2h, then left to stand for 2h, filtered, washed with deionized water for 3 times, and dried in an oven at 70℃ for 10min to obtain calcium carbonate particles loaded with nanosheets; the mass ratio of zinc nitrate hexahydrate, deionized water, potassium hydroxide, calcium carbonate particles and dodecyltrimethylammonium bromide is 3.4:110:1.6:5:0.7; A2. Add tannic acid into ethanol, stir until completely dissolved, add carbon fiber, stir at 50℃ for 30min, add calcium carbonate particles loaded with nanosheets, stir at 25℃, 800r / min for 40min, filter, wash with deionized water for 3 times, dry in oven at 70℃ for 10min, to obtain modified carbon fiber; the mass ratio of tannic acid, ethanol, carbon fiber and calcium carbonate particles loaded with nanosheets is 1:50:4.5:2.9; A3. Mix graphene oxide and n-butylamine, stir at 60℃ for 1h, add toluene, ultrasonic treatment at 20KHz for 30min, add γ-methacryloxypropyltrimethoxysilane, continue ultrasonic treatment for 30min, then stir at 110℃ for 4h, collect the precipitate by centrifugation, wash the precipitate with ethanol for 3 times, wash with acetone for 3 times, dry in oven at 60℃ for 12h, to obtain modified graphene oxide; the mass ratio of graphene oxide, n-butylamine, toluene and γ-methacryloxypropyltrimethoxysilane is 1.6:17:90:4; A4. Add modified carbon fiber and γ-methacryloxypropyltrimethoxysilane into ethanol and deionized water, stir at 60℃ for 2h, cool to room temperature, filter, wash with deionized water for 3 times, then dry in oven at 70℃ for 10min, to obtain double bond modified carbon fiber; the mass ratio of modified carbon fiber, γ-methacryloxypropyltrimethoxysilane, ethanol and deionized water is 5:0.8:30:12; A5. Add double bond modified carbon fiber, modified graphene oxide and lauryl methacrylate into ethanol, stir uniformly, add azobisisobutyronitrile, pass nitrogen, stir at 300r / min, 60℃ for 4h, filter, wash with deionized water for 3 times, then dry in oven at 70℃ for 10min, to obtain anti-skid wear-resistant filler; the mass ratio of double bond modified carbon fiber, modified graphene oxide, lauryl methacrylate, ethanol and azobisisobutyronitrile is 5:4:4.5:150:0.3.
[0047] Comparative Example 1 An environment-friendly anti-skid plastic track material, comprising the following raw materials in parts by mass: hyperbranched polyethylene 55 parts, anti-skid wear-resistant filler 15 parts, styrene-ethylene-butylene-styrene block copolymer 8 parts, talc 50 parts, AC foaming agent 2 parts, stearic acid 2 parts; A preparation method of an environment-friendly anti-skid plastic track material, comprising the following preparation steps: S1. Mix hyperbranched polyethylene, anti-skid wear-resistant filler, styrene-ethylene-butylene-styrene block copolymer, talc, AC foaming agent and stearic acid uniformly, the mixing temperature is 80℃, the mixing time is 10min, and the mixing speed is 800r / min, to obtain a mixture; S2. The mixture is extruded and granulated to obtain the anti-skid plastic track material. The extrusion is performed by using a double screw extruder, the temperature of the extruder barrel and die head is 200℃, and the screw rotation speed is 500r / min.
[0048] The anti-skid wear-resistant filler is prepared by the following steps: A1. Tannic acid is added to ethanol and stirred until completely dissolved. Carbon fibers are added and stirred at 50℃ for 30min. Calcium carbonate particles are added and stirred at 25℃ and 800r / min for 40min. After filtration, the product is washed with deionized water for 3 times and dried in an oven at 70℃ for 10min to obtain modified carbon fibers. The mass ratio of tannic acid, ethanol, carbon fibers and calcium carbonate particles is 1:50:4.5:2.9; A2. Graphene oxide and n-butylamine are mixed and stirred at 60℃ for 1h. Toluene is added and ultrasonically treated at 20KHz for 30min. γ-methacryloxypropyltrimethoxysilane is added and ultrasonically treated for another 30min. After stirring at 110℃ for 4h, the precipitate is collected by centrifugation, washed with ethanol for 3 times and with acetone for 3 times, and dried in an oven at 60℃ for 12h to obtain modified graphene oxide. The mass ratio of graphene oxide, n-butylamine, toluene and γ-methacryloxypropyltrimethoxysilane is 1.6:17:90:4; A3. Modified carbon fibers and γ-methacryloxypropyltrimethoxysilane are added to ethanol and deionized water, and stirred at 60℃ for 2h. After cooling to room temperature, the product is filtered, washed with deionized water for 3 times and dried in an oven at 70℃ for 10min to obtain double bond modified carbon fibers. The mass ratio of modified carbon fibers, γ-methacryloxypropyltrimethoxysilane, ethanol and deionized water is 5:0.8:30:12; A4. Double bond modified carbon fibers, modified graphene oxide and lauryl methacrylate are added to ethanol and stirred uniformly. Azobisisobutyronitrile is added and stirred at 300r / min and 60℃ for 4h. After filtration, the product is washed with deionized water for 3 times and dried in an oven at 70℃ for 10min to obtain the anti-skid wear-resistant filler. The mass ratio of double bond modified carbon fibers, modified graphene oxide, lauryl methacrylate, ethanol and azobisisobutyronitrile is 5:4:4.5:150:0.3.
[0049] Comparative Example 2 An environmentally friendly anti-skid plastic track material, comprising the following raw materials in mass parts: hyperbranched polyethylene 55 parts, anti-skid wear-resistant filler 15 parts, styrene-ethylene-butylene-styrene block copolymer 8 parts, talc 50 parts, AC foaming agent 2 parts, and stearic acid 2 parts; A method for preparing an environmentally friendly anti-skid plastic track material, comprising the following preparation steps: S1. Mix the hyperbranched polyethylene, anti-skid wear-resistant filler, styrene-ethylene-butylene-styrene block copolymer, talcum powder, AC foaming agent, and stearic acid uniformly, the mixing temperature is 80℃, the mixing time is 10min, and the mixing speed is 800r / min, to obtain a mixture; S2. Extrude and granulate the mixture to obtain the anti-skid plastic track material, the extrusion is performed by using a double screw extruder, the temperature of the extruder barrel and die head is 200℃, and the screw rotation speed is 500r / min.
[0050] The anti-skid wear-resistant filler is prepared by the following steps: A1. Add zinc nitrate hexahydrate into deionized water, stir uniformly, heat to 80℃, add potassium hydroxide and calcium carbonate particles, stir and mix for 30min, add dodecyl trimethyl ammonium bromide, continue to stir for 2h, stand for 2h, filter, wash with deionized water for 3 times, and dry in a 70℃ oven for 10min to obtain calcium carbonate particles loaded with nanosheets; the mass ratio of zinc nitrate hexahydrate, deionized water, potassium hydroxide, calcium carbonate particles and dodecyl trimethyl ammonium bromide is 3.4:110:1.6:5:0.7; A2. Mix ethanol and carbon fibers, stir at 50℃ for 30min, add calcium carbonate particles loaded with nanosheets, stir at 25℃ and 800r / min for 40min, filter, wash with deionized water for 3 times, and dry in a 70℃ oven for 10min to obtain modified carbon fibers; the mass ratio of ethanol, carbon fibers and calcium carbonate particles loaded with nanosheets is 51:4.5:2.9; A3. Mix graphene oxide and n-butylamine, stir at 60℃ for 1h, add toluene, ultrasonically treat at 20KHz for 30min, add γ-methacryloxypropyl trimethoxysilane, continue to ultrasonically treat for 30min, then stir and react at 110℃ for 4h, collect the precipitate by centrifugation, wash the precipitate with ethanol for 3 times, wash with acetone for 3 times, and dry in a 60℃ oven for 12h to obtain modified graphene oxide; the mass ratio of graphene oxide, n-butylamine, toluene and γ-methacryloxypropyl trimethoxysilane is 1.6:17:90:4; A4. Add modified carbon fibers and γ-methacryloxypropyl trimethoxysilane into ethanol and deionized water, stir and react at 60℃ for 2h, cool to room temperature, filter, wash with deionized water for 3 times, and dry in a 70℃ oven for 10min to obtain double bond modified carbon fibers; the mass ratio of modified carbon fibers, γ-methacryloxypropyl trimethoxysilane, ethanol and deionized water is 5:0.8:30:12; A5. The double bond modified carbon fiber, modified graphene oxide and lauryl methacrylate are added to ethanol, stirred uniformly, azobisisobutyronitrile is added, nitrogen is introduced, stirring is carried out at 300 r / min and 60℃ for 4h, after filtration, deionized water is washed for 3 times, and then drying is carried out in a 70℃ oven for 10 min to obtain the anti-skid wear-resistant filler; the mass ratio of the double bond modified carbon fiber, modified graphene oxide, lauryl methacrylate, ethanol and azobisisobutyronitrile is 5:4:4.5:150:0.3.
[0051] Comparative Example 3 An environmentally friendly anti-skid plastic track material, comprising the following raw materials in parts by mass: hyperbranched polyethylene 55 parts, anti-skid wear-resistant filler 15 parts, styrene-ethylene-butylene-styrene block copolymer 8 parts, talc 50 parts, AC foaming agent 2 parts, stearic acid 2 parts. A method for preparing an environmentally friendly anti-skid plastic track material, comprising the following preparation steps: S1. The hyperbranched polyethylene, anti-skid wear-resistant filler, styrene-ethylene-butylene-styrene block copolymer, talc, AC foaming agent and stearic acid are uniformly mixed, the mixing temperature is 80℃, the mixing time is 10 min, and the mixing speed is 800 r / min to obtain a mixture; S2. The mixture is extruded and granulated to obtain the anti-skid plastic track material, and a double screw extruder is used for extrusion, the barrel and die head temperature of the extruder is 200℃, and the screw rotation speed is 500 r / min.
[0052] The anti-skid wear-resistant filler is specifically prepared by the following steps: A1. Zinc nitrate hexahydrate is added to deionized water, stirred uniformly, heated to 80℃, potassium hydroxide and calcium carbonate particles are added, stirred and mixed for 30 min, dodecyltrimethylammonium bromide is added, and stirring is continued for 2h, and then the mixture is left to stand for 2h, filtered, washed with deionized water for 3 times, and dried in a 70℃ oven for 10 min to obtain calcium carbonate particles loaded with nanosheets; the mass ratio of zinc nitrate hexahydrate, deionized water, potassium hydroxide, calcium carbonate particles and dodecyltrimethylammonium bromide is 3.4:110:1.6:5:0.7; A2. Tannic acid is added to ethanol, stirred until completely dissolved, carbon fiber is added, stirring is carried out at 50℃ for 30 min, calcium carbonate particles loaded with nanosheets are added, stirring is carried out at 25℃ and 800 r / min for 40 min, then the mixture is filtered, washed with deionized water for 3 times, and dried in a 70℃ oven for 10 min to obtain modified carbon fiber; the mass ratio of tannic acid, ethanol, carbon fiber and calcium carbonate particles loaded with nanosheets is 1:50:4.5:2.9; A3. The modified carbon fiber, γ-methacryloxypropyltrimethoxysilane is added to ethanol and deionized water, stirred and reacted at 60℃ for 2h, cooled to room temperature, filtered, washed with deionized water for 3 times, and dried in an oven at 70℃ for 10min to obtain a double bond modified carbon fiber; the mass ratio of the modified carbon fiber, γ-methacryloxypropyltrimethoxysilane, ethanol and deionized water is 5:0.8:30:12; A4. The double bond modified carbon fiber, graphene oxide and lauryl methacrylate are added to ethanol, stirred and mixed uniformly, azobisisobutyronitrile is added, nitrogen is introduced, stirred and reacted at 300r / min and 60℃ for 4h, filtered, washed with deionized water for 3 times, and dried in an oven at 70℃ for 10min to obtain an anti-skid wear-resistant filler; the mass ratio of the double bond modified carbon fiber, graphene oxide, lauryl methacrylate, ethanol and azobisisobutyronitrile is 5:4:4.5:150:0.3.
[0053] Comparative Example 4 An environmentally friendly anti-skid plastic track material, comprising the following raw materials in parts by mass: hyperbranched polyethylene 55 parts, anti-skid wear-resistant filler 15 parts, styrene-ethylene-butylene-styrene block copolymer 8 parts, talc 50 parts, AC foaming agent 2 parts, stearic acid 2 parts; A preparation method of an environmentally friendly anti-skid plastic track material, comprising the following preparation steps: S1. The hyperbranched polyethylene, anti-skid wear-resistant filler, styrene-ethylene-butylene-styrene block copolymer, talc, AC foaming agent and stearic acid are uniformly mixed, the mixing temperature is 80℃, the mixing time is 10min, and the mixing speed is 800r / min to obtain a mixture; S2. The mixture is extruded and granulated to obtain an anti-skid plastic track material, and a double screw extruder is used for extrusion, the barrel and die head temperature of the extruder is 200℃, and the screw rotation speed is 500r / min.
[0054] The anti-skid wear-resistant filler is specifically prepared by the following steps: A1. Zinc nitrate hexahydrate is added to deionized water, stirred and mixed uniformly, heated to 80℃, potassium hydroxide and calcium carbonate particles are added, stirred and mixed for 30min, dodecyltrimethylammonium bromide is added, and stirred for another 2h, then left to stand for 2h, filtered, washed with deionized water for 3 times, and dried in an oven at 70℃ for 10min to obtain calcium carbonate particles loaded with nanosheets; the mass ratio of zinc nitrate hexahydrate, deionized water, potassium hydroxide, calcium carbonate particles and dodecyltrimethylammonium bromide is 3.4:110:1.6:5:0.7; A2. Tannic acid was added into ethanol, stirred until completely dissolved, carbon fiber was added, stirred at 50℃ for 30min, calcium carbonate particles loaded with nanosheets were added, stirred at 25℃, 800r / min for 40min, filtered, washed with deionized water for 3 times, dried in an oven at 70℃ for 10min to obtain modified carbon fiber; the mass ratio of tannic acid, ethanol, carbon fiber and calcium carbonate particles loaded with nanosheets was 1:50:4.5:2.9; A3. Graphene oxide and n-butylamine were mixed, stirred at 60℃ for 1h, toluene was added, ultrasonically treated at 20KHz for 30min, γ-methacryloxypropyltrimethoxysilane was added, continued to ultrasonically treat for 30min, then stirred at 110℃ for 4h, the precipitate was collected by centrifugation, the precipitate was washed with ethanol for 3 times, washed with acetone for 3 times, dried in an oven at 60℃ for 12h to obtain modified graphene oxide; the mass ratio of graphene oxide, n-butylamine, toluene and γ-methacryloxypropyltrimethoxysilane was 1.6:17:90:4; A4. Modified carbon fiber, modified graphene oxide and lauryl methacrylate were added into ethanol, stirred uniformly, azobisisobutyronitrile was added, nitrogen was introduced, stirred at 300r / min, 60℃ for 4h, filtered, washed with deionized water for 3 times, then dried in an oven at 70℃ for 10min to obtain anti-skid and wear-resistant filler; the mass ratio of modified carbon fiber, modified graphene oxide, lauryl methacrylate, ethanol and azobisisobutyronitrile was 5:4:4.5:150:0.3.
[0055] Comparative Example 5 An environment-friendly anti-skid plastic track material, comprising the following raw materials in parts by mass: hyperbranched polyethylene 55 parts, anti-skid and wear-resistant filler 15 parts, styrene-ethylene-butylene-styrene block copolymer 8 parts, talc 50 parts, AC foaming agent 2 parts, stearic acid 2 parts; A preparation method of an environment-friendly anti-skid plastic track material, comprising the following preparation steps: S1. Hyperbranched polyethylene, anti-skid and wear-resistant filler, styrene-ethylene-butylene-styrene block copolymer, talc, AC foaming agent and stearic acid were mixed uniformly, the mixing temperature was 80℃, the mixing time was 10min, and the mixing speed was 800r / min to obtain a mixture; S2. The mixture was extruded and granulated to obtain an anti-skid plastic track material, a double-screw extruder was used for extrusion, the temperature of the extruder barrel and die head was 200℃, and the screw rotation speed was 500r / min.
[0056] The anti-skid and wear-resistant filler was prepared by the following steps: A1. Zinc nitrate hexahydrate was added to deionized water, stirred uniformly, heated to 80°C, potassium hydroxide and calcium carbonate particles were added, stirred for 30 min, dodecyl trimethyl ammonium bromide was added, continued to stir for 2 h, stood for 2 h, filtered, washed with deionized water for 3 times, dried in an oven at 70°C for 10 min, to obtain calcium carbonate particles loaded with nanosheets; the mass ratio of zinc nitrate hexahydrate, deionized water, potassium hydroxide, calcium carbonate particles and dodecyl trimethyl ammonium bromide was 3.4:110:1.6:5:0.7; A2. Tannic acid was added to ethanol, stirred until completely dissolved, carbon fibers were added, stirred at 50°C for 30 min, calcium carbonate particles loaded with nanosheets were added, stirred at 25°C, 800 r / min for 40 min, filtered, washed with deionized water for 3 times, dried in an oven at 70°C for 10 min, to obtain modified carbon fibers; the mass ratio of tannic acid, ethanol, carbon fibers and calcium carbonate particles loaded with nanosheets was 1:50:4.5:2.9; A3. Graphene oxide and n-butylamine were mixed, stirred at 60°C for 1 h, toluene was added, ultrasonically treated at 20 KHz for 30 min, γ-methacryloxypropyl trimethoxysilane was added, continued to ultrasonically treat for 30 min, then stirred at 110°C for 4 h, the precipitate was collected by centrifugation, the precipitate was washed with ethanol for 3 times, washed with acetone for 3 times, dried in an oven at 60°C for 12 h, to obtain modified graphene oxide; the mass ratio of graphene oxide, n-butylamine, toluene and γ-methacryloxypropyl trimethoxysilane was 1.6:17:90:4; A4. Modified carbon fibers and γ-methacryloxypropyl trimethoxysilane were added to ethanol and deionized water, stirred at 60°C for 2 h, cooled to room temperature, filtered, washed with deionized water for 3 times, dried in an oven at 70°C for 10 min, to obtain double bond modified carbon fibers; the mass ratio of modified carbon fibers, γ-methacryloxypropyl trimethoxysilane, ethanol and deionized water was 5:0.8:30:12; A5. Double bond modified carbon fibers and modified graphene oxide were added to ethanol, stirred uniformly, azobisisobutyronitrile was added, nitrogen was introduced, stirred at 300 r / min, 60°C for 4 h, filtered, washed with deionized water for 3 times, dried in an oven at 70°C for 10 min, to obtain anti-skid wear-resistant filler; the mass ratio of double bond modified carbon fibers, modified graphene oxide, ethanol and azobisisobutyronitrile was 5:4:154.5:0.3.
[0057] The anti-skid plastic runway materials prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to performance detection.
[0058] The anti-skid plastic runway materials prepared above had a particle size of 5 mm.
[0059] The anti-skid plastic track material prepared above and PU glue are mixed in a mass ratio of 6:1, stirred uniformly, laid flat, and then pressed to be compacted and bonded to form a coiled material with a thickness of 13 mm and a smooth surface, i.e. an anti-skid plastic track.
[0060] The anti-skid performance, vertical deformation, impact absorption, tensile strength and friction coefficient of the anti-skid plastic track are tested according to the method specified in GB / T 14833-2020 "Synthetic material sports ground surface layer".
[0061] As shown in Table 1 below.
[0062] Table 1 Performance test of anti-skid plastic track material prepared in Examples 1-3 and Comparative Examples 1-5 As can be seen from the data in Table 1, the anti-skid plastic track material prepared in Examples 1-3 has good anti-skid wear resistance and mechanical strength.
[0063] In Comparative Example 1, the anti-skid wear-resistant filler prepared by replacing the calcium carbonate particles loaded with nanosheets with calcium carbonate particles is added to the anti-skid plastic track material, and the anti-skid performance decreases, proving that the petal-shaped zinc oxide nanosheets synthesized on the surface of the calcium carbonate particles can play a "mechanical interlocking" effect, can generate greater resistance, increase the friction coefficient, and thus enhance the anti-skid performance of the plastic track material. The three-dimensional structure of the petal-shaped zinc oxide nanosheets formed by the interlaced connection of nanosheets can effectively disperse pressure, reduce local wear, and improve the wear resistance of the plastic track material.
[0064] In Comparative Example 2, the anti-skid wear-resistant filler prepared by replacing tannic acid with ethanol is added to the anti-skid plastic track material, and the anti-skid performance and mechanical properties decrease, proving that the calcium carbonate particles loaded with nanosheets are deposited on the surface of the carbon fibers by tannic acid, and the carbon fibers form a network structure that can absorb and weaken external pressure, which can avoid the petal-shaped zinc oxide nanosheets with a relatively thin thickness, which are prone to breakage and shedding during long-term use, affecting the anti-skid wear resistance of the plastic track material. In addition, carbon fibers have high tensile strength and elastic modulus, and when added to the plastic track material, they can significantly enhance the impact resistance and load-bearing capacity of the plastic track.
[0065] In Comparative Example 3, the anti-skid wear-resistant filler prepared by replacing modified graphene oxide with graphene oxide is added to the anti-skid plastic track material, and the anti-skid performance decreases, proving that the graphene oxide is intercalated with γ-methacryloxypropyltrimethoxysilane and silanized on the surface, maintaining the layered structure of the graphene oxide and improving the wear resistance of the plastic track material. In addition, it is conducive to the covalent grafting of graphene oxide on the surface of modified carbon fibers, producing a micro-roller effect, and thus enhancing the wear resistance of the plastic track material.
[0066] The anti-skid and wear-resistant filler prepared by replacing the double-bond modified carbon fiber with the modified carbon fiber in Comparative Example 4 is added into the anti-skid plastic track material, and the anti-skid performance and mechanical properties thereof are reduced, which proves that the double-bond modified carbon fiber can copolymerize with the modified carbon fiber and lauryl methacrylate, so that the modified graphene oxide is coated on the surface of the modified carbon fiber through the terpolymer, the terpolymer between the layers acts as a lubricating component, so that the modified graphene oxide moves back and forth on the surface of the modified carbon fiber, generates a micro-rolling ball effect, increases the buffer distance of the modified graphene oxide and the modified carbon fiber, and thus reduces the heat generated by friction of the composite material, and has excellent wear-resistant effect.
[0067] The anti-skid and wear-resistant filler prepared by replacing lauryl methacrylate with ethanol in Comparative Example 5 is added into the anti-skid plastic track material, and the anti-skid performance and mechanical properties thereof are reduced, which proves that the long carbon molecular chain of lauryl methacrylate in the terpolymer can penetrate into the gap between the nanosheets, form an entangled network, and improve the shear resistance, so as to avoid the structure damage of the anti-skid and wear-resistant filler caused by strong shear force during friction, and affect the anti-skid, wear-resistant performance and mechanical properties of the plastic track material.
[0068] In the description of the specification, the description of the terms "one embodiment", "example", "specific example" and the like means that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0069] The above is only an example and description of the present application, and those skilled in the art can make various modifications or supplements to the described specific embodiments or use similar ways to replace, as long as they do not deviate from the invention or exceed the scope defined by the present claims, which shall belong to the protection scope of the present application.
Claims
1. An environmentally friendly anti-skid plastic runway material, characterized in that: The invention comprises the following raw materials in parts by weight: 50-55 parts of hyperbranched polyethylene, 10-15 parts of anti-skid and wear-resistant filler, 5-8 parts of plastic toughening agent, 45-50 parts of inorganic filler, 1-2 parts of plastic foaming agent, and 1-2 parts of dispersant; Among them, the anti-slip and wear-resistant filler is obtained by treating graphene oxide with silane, and then mixing and reacting with silane, modified carbon fiber and lauryl methacrylate; The modified carbon fiber is obtained by synthesizing zinc oxide nanosheets on the surface of calcium carbonate particles and then depositing them on the carbon fiber surface through tannic acid.
2. The environmentally friendly anti-skid plastic track material according to claim 1, characterized in that: The anti-skid and wear-resistant filler is specifically prepared by the following steps: A1. Zinc nitrate hexahydrate was added to deionized water and stirred. The mixture was heated to 70-80°C, potassium hydroxide and calcium carbonate particles were added, and the mixture was stirred. Dodecyltrimethylammonium bromide was added and the mixture was stirred. The mixture was allowed to stand for 1 h, filtered, washed, and dried to obtain calcium carbonate particles loaded with nanosheets. A2. Tannic acid was added to ethanol and stirred until completely dissolved. Carbon fibers were added. After stirring, calcium carbonate particles loaded with nanosheets were added. Stirring was continued, and the mixture was filtered, washed, and dried to obtain modified carbon fibers. A3. Graphene oxide and n-butylamine were mixed and stirred, toluene was added, and the mixture was ultrasonically treated. Silane was added and ultrasonicated. The mixture was stirred and reacted. The precipitate was collected by centrifugation, washed, and dried to obtain modified graphene oxide. A4. The modified carbon fiber and silane were added to ethanol and deionized water, and after the reaction was completed with stirring, the mixture was cooled to room temperature, filtered, washed, and dried to obtain a double-bonded modified carbon fiber; A5. Add double-bonded modified carbon fiber, modified graphene oxide, and lauryl methacrylate to ethanol, stir evenly, add azobisisobutyronitrile, introduce nitrogen, stir to react, filter, wash, and dry to obtain a non-slip and wear-resistant filler.
3. The environmentally friendly anti-skid plastic track material according to claim 2, characterized in that: In step A1, the mass ratio of zinc nitrate hexahydrate, deionized water, potassium hydroxide, calcium carbonate particles and dodecyltrimethylammonium bromide is (3-3.4):(90-110):(1.2-1.6):(4-5):(0.3-0.7).
4. The environmentally friendly anti-skid plastic track material according to claim 2, characterized in that: In step A2, the mass ratio of the tannic acid, ethanol, carbon fiber and nanosheet-loaded calcium carbonate particles is (0.6-1):(45-50):(4-4.5):(2.5-2.9).
5. The environmentally friendly anti-skid plastic track material according to claim 2, characterized in that: In step A3, the mass ratio of graphene oxide, n-butylamine, toluene and silane is (1.4-1.6):(13-17):(80-90):(3-4).
6. The environmentally friendly anti-skid plastic track material according to claim 2, characterized in that: In step A4, the mass ratio of the modified carbon fiber, silane, ethanol and deionized water is (4-5):(0.6-0.8):(25-30):(8-12).
7. The environmentally friendly anti-skid plastic track material according to claim 2, characterized in that: In step A5, the mass ratio of the double-bonded modified carbon fiber, modified graphene oxide, lauryl methacrylate, ethanol and azobisisobutyronitrile is (4-5):(3-4):(4-4.5):(130-150):(0.1-0.3).
8. The environmentally friendly anti-skid plastic track material according to claim 1, characterized in that: The plastic toughening agent is selected from styrene-ethylene-butylene-styrene block copolymer or styrene-butadiene-styrene block copolymer; The inorganic filler is selected from any one of talc, kaolin and white carbon black.
9. The environmentally friendly anti-skid plastic track material according to claim 1, characterized in that: The plastic foaming agent is an AC foaming agent or an ADC foaming agent; The dispersant is stearic acid or glyceryl stearate.
10. A method for preparing the environmentally friendly anti-skid plastic track material according to any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: S1. The hyperbranched polyethylene, anti-slip and wear-resistant filler, plastic toughening agent, inorganic filler, plastic foaming agent, dispersant are mixed to obtain a mixture; S2. The mixed material is extruded and granulated to obtain an anti-slip plastic track material.
Citation Information
Cited By
High-performance yellowing-resistant plastic track material and preparation method thereof
CN121203278A